Different Phenotypes at Onset in Neuromyelitis Optica Spectrum Disorder Patients with Aquaporin-4 Autoimmunity - Long, Youming; Liang, Junyan; Wu, Linzhan; Lin, Shaopeng; Gao, Cong; Chen, Xiaohui; Qiu, Wei; Yang, Yu; Zheng, Xueping; Yang, Ning; Gao, Min; Chen, Yaotang; et al. (Frontiers in Neurology, 2017)
Background Although rare, brain abnormalities without optic neuritis (ON) or transverse myelitis (TM) diagnosed with neuromyelitis optica spectrum disorder (NMOSD) have been reported in patients positive for the aquaporin-4 (AQP4) antibody. Objective To analyze demographic and clinical differences among NMOSD patients without ON or TM, those with either ON or TM, and patients with simultaneous ON and TM at disease onset. Methods In this retrospective study, patients who were positive for the AQP4 antibody, as detected using a cell-based assay, at the Second Affiliated Hospital of Guangzhou Medical University in China were recruited. Demographic and clinical data were obtained from each patient’s medical record. Results A total of 292 patients were included in this study and were divided into four subgroups based on their initial manifestations: (i) NMOSD without ON or TM (NMOSD-ON−TM−, n = 70); (ii) NMOSD with ON (NMOSD-ON+, n = 95); (iii) NMOSD with TM (NMOSD-TM+, n = 116); and (iv) simultaneous ON and TM [neuromyelitis optica (NMO), n = 11]. We found that age at onset was lower in the NMOSD-ON−TM− group than that in the other groups. The interval from the first episode to relapse was shorter in the NMOSD-ON−TM− group than that in NMOSD-TM+ group. Cerebral spinal fluid white cell counts and protein levels were significantly higher in the NMOSD-ON−TM− group than those in the other groups. Lower Expanded Disability Status Scale scores were observed in the NMOSD-ON−TM− group. Brain abnormalities, including in area postrema and hemisphere lesions, were more frequent in the NMOSD-ON−TM− group. Kaplan–Meier analysis showed that patients in the NMOSD-ON−TM− group experienced earlier relapse than those in other groups. Conversion to NMO in the NMOSD-ON+ group was greater than that in the other groups. Only 14 patients (4.8%, 14/292) had pure brain abnormalities, of which 12 had disease duration of several more years and 8 (57.1%) experienced relapses. Conclusion NMOSD patients with different initial manifestations present with significant differences in clinical features during follow-up. Patients with long-term AQP4 autoimmunity in the brain in the absence of ON or TM are not common.